SKREENING HIPERTENSI DAN ANEMIA MELALUI BAKTI SOSIAL PEMERIKSAAN TEKANAN DARAH DAN HEMOGLOBIN PADA WANITA USIA SUBUR - Dyah Muliawati; Nihlah Zati Bayani (LPPM STIKES Madani Yogyakarta, 2019)
Based on the report of the Integrated System for Communicable Diseases in Yogyakarta Health Center, in 2015 there were 256,586 people aged> 15 years and based on the number of patient visits to the primary health center and screening, the risk factors for non-communicable diseases is outside the building. Hypertension measurements were conducted to 7,464 (18.49%) patients. Hypertension cases in people aged> 15 years were more common in women (63.96%) compared to men (36.04%). The anemia prevalence of childbearing age Women is the most risky, with the prevalence of anemia in non-pregnant women aged 15-49 by 30%. Sleman Regency is a large area in Yogyakarta, so not all villages have a specific approach to health. A mother will give birth to the next generation so that more special attention is needed, for example by screening blood pressure and HB levels. One of the villages in Sleman Regency is Sindumartani Village, the majority of the population is farmer and the majority of wives is Housewife and is helping work in the fields. The residents of Sindumartani Village are still lay about anemia and hypertension. The method used is blood pressure examination using digital spygmomanometer and HB examination with digital devices. The blood pressure examinations on 22 mothers shows 16 (72.72%) mothers were not hypertensive, and HB examination on 19 mothers show 12 (63.15%) mothers were not anemic.